2019
DOI: 10.1001/jamanetworkopen.2019.4186
|View full text |Cite
|
Sign up to set email alerts
|

Association of Breastfeeding and Air Pollution Exposure With Lung Function in Chinese Children

Abstract: This cross-sectional study evaluates the association of air pollution exposure and having been breastfed or not with lung function among children in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
35
1

Year Published

2019
2019
2022
2022

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 49 publications
2
35
1
Order By: Relevance
“…Exclusivity of breastfeeding was also studied and showed protective effects on neurodevelopment [73,74]. Mainly breastfeeding for 3 months was shown to decrease the adverse impact of air pollution on respiratory health [11], lung function [13], and blood pressure [84]. However, the duration of predominately breastfeeding showed no effect on neurodevelopmental outcomes with prenatal exposure to PM 2.5 and NO 2 [12].…”
Section: Findings and Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…Exclusivity of breastfeeding was also studied and showed protective effects on neurodevelopment [73,74]. Mainly breastfeeding for 3 months was shown to decrease the adverse impact of air pollution on respiratory health [11], lung function [13], and blood pressure [84]. However, the duration of predominately breastfeeding showed no effect on neurodevelopmental outcomes with prenatal exposure to PM 2.5 and NO 2 [12].…”
Section: Findings and Discussionmentioning
confidence: 99%
“…Also, it remains unclear how long the protective effects of breastfeeding persist. Several of the analyzed studies showed that the protective action of breastfeeding may diminish with age, but further studies are necessary [11,13,79]. Moreover, the exact mechanisms of modifying breastfeeding actions remain unclear; nonetheless, several possible explanations have been proposed.…”
Section: Findings and Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…We are interested in reports of original research on the associations of heat with the health of humans 3 and their potential adaptations to global warming. 4 Air pollution is a critically important topic because it is associated with increases in the risk of cardiovascular disease, 5,6 impaired lung function, 7 allergies and asthma, altered thyroid function, 8 food insecurity and malnutrition, and forced migration. The increasing incidence of wildfires further lessens air quality and has immediate and long-term effects on humans and other organisms.…”
mentioning
confidence: 99%